Suweg Flour (Amorphophallus Campanulatus) Potential Reducing TNF-Î± Levels in Model Diabetic Rats - Setyawati, Ika (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Diabetes mellitus (DM) is a chronic disease and it is called as a silent killer because this disease is unrecognized by the diabetics. However, when it is already known the complication is occurred. It is recognized by the increase of blood glucose level (hyperglycemia) as the main character of Diabetes Mellitus (DM). This condition causes the increase of the Reactive Oxygen Species (ROS) in a chronic condition.Â  Then, insulin resistance is caused by the oxidative stress in fat, muscle and liver tissue. Moreover, insulin resistance produces several oxidative stress mediators includingÂ  (TNF- Î±). This research aims to determine the effect of suweg flour (Amorphophallus campanulatus) on TNF-Î± level in rats diabetic model. The method used in the research was an experimental laboratory of pre-post control group test conducted in 28 days. The subjects of this research were 25 Rattus Novergicus wistar strains, (P1) positif control (P2), standart (P3) and two treatment groups (P4 and P5). The data were gained by measuring the level of TNF-Î± before and after receiving the suweg flour enzyme-linked immunosorbent assay (ELISA). The data were analyzed by paired sample t-test. This research showed a significant correlation between suweg flour and TNF-Î± levels (p = 0.000). A significant correlation was discovered in all treatment groups (P4 and P5). The results of this research can be concluded that the administration of suweg flour (Amorphophallus campanulatus) can decrease of TNF-Î± levels in rats diabetic model.